Educational Management in Islamic Boarding Schools: Enhancing Students’ Religious Character in Indonesian Senior High Schools - Febri Aris Susanto; Moh. Padil; Achmad Fattah Yasin; Syarifaturrahmatullah Syarifaturrahmatullah; Afga Sidiq Rifai; Iri Hamzah; Bunayar Bunayar; Bima Fandi Asy’arie (STAI Hubbulwathan Duri, 2025)
Religious character development in students is a central goal of Islamic education, particularly within institutions adopting a boarding school-based management model. This study investigates how such a model supports the cultivation of students’ religious character at SMA Muhammadiyah 2 Sidoarjo, East Java. Using a qualitative case study approach, data were collected through observation, interviews, and document analysis. The study focused on three core aspects of educational management: planning, implementation, and evaluation, within the boarding school context. The planning process aligns closely with the school’s vision, mission, and institutional goals, incorporating character values such as discipline, responsibility, independence, politeness, and religious worship. Implementation involves the integration of these values across all school activities, including formal subjects, extracurriculars, daily routines, and role modeling by teachers and boarding supervisors. Evaluation is conducted through supervision, identification of challenges, reporting, and formulation of follow-up actions, ensuring continuous improvement in character formation. Boarding school-based education management creates a structured and spiritually enriched environment that reinforces students' moral and religious development. By embedding character education within all aspects of school life, the model fosters sustainable internalization of Islamic values. This integrated approach proves effective in cultivating religious character through habit formation and consistent reinforcement.